Primords of latin american codification on private international law - Briceño Berrú, José Enrique (2023)
This article traces the evolution of the codification of Private International Law in Latin America, from Simón Bolívar’s early attempts in 1826 to the Pan-American conferences of the 20th century, highlighting milestones such as the Panama Congress in 1826 and the Montevideo Congress in 1888- 1889. It explores the transition from the concept of legislative uniformity to the harmonization of conflict rules. Additionally, it examines the influence of political and migratory factors, as well as the stances of countries like Argentina, Brazil, and Chile, in adopting principles such as nationality and domicile. This historical analysis reflects continental solidarity and underscores Latin America’s unique contribution to the development of conventional Private International Law.